Juvenile Gaucher's disease with horizontal gaze palsy in three siblings. Issue 5 (May 1977) - Tripp, J H; Lake, B D; Young, E; Ngu, J; Brett, E M
Abstract : Three children in a West African family had Gaucher's disease of juvenile onset (Type 3), and all showed an identical neurological disorder. The diagnosis was substantiated by histochemical demonstration of Gaucher cells in bone marrow, liver, and spleen, the finding of an excess of glucosyl ceramides in a liver extract, and a deficient activity of the enzyme beta-glucosidase in cultured skin fibroblasts. The neurological picture was characterised by myoclonic epilepsy, muscle wasting, hypotonia, pyramidal signs, some intellectual deterioration, and a striking disturbance of eye movements. The latter appears to result from specific involvement of the supranuclear pathways subserving lateral gaze. The distinctive features of this clinical syndrome are emphasised.